The WEIRDest people in the world : how the West became psychologically peculiar and particularly prosperous - Henrich, Joseph Patrick (Farrar, Straus and Giroux, 2020)
"Harvard University's Joseph Henrich, Chair of the Department of Human Evolutionary Biology, delivers a bold, epic investigation into the development of the Western mind, global psychological diversity, and its impact on the world"--